Involuntary weight loss in elderly individuals: assessment and treatment - Moriguti, Julio Cesar; Moriguti, Eny Kiyomi Uemura; Ferriolli, Eduardo; Cação, João de Castilho; Iucif Junior, Nelson; Marchini, Julio Sergio (São Paulo Medical Journal, 2001)
CONTEXT: The loss of body weight and fat late in life is associated with premature death and increased risk of disability, even after excluding elderly subjects who have a preexisting disease. Although it is important to recognize that periods of substantially positive or negative energy balance and body weight fluctuation occur as a normal part of life, weight losses greater than 5% over 6 months should be investigated. We can divide the major causes of weight loss in the elderly into 4 categories: social, psychiatric, due to medical conditions, and age-related. The clinical evaluation should include a careful history and physical examination. If these fail to provide clues to the weight loss, simple diagnostic tests are indicated. A period of watchful waiting is preferable to blind pursuit of additional diagnostic testing that may yield few useful data, if the results of these initial tests are normal. The first step in managing patients with weight loss is to identify and treat any specific causative or contributing conditions and to provide nutritional support when indicated. Non-orexigenic drugs have found an established place in the management of protein-energy malnutrition. Early attention to nutrition and prevention of weight loss during periods of acute stress, particularly during hospitalization, may be extremely important, as efforts directed at re-feeding are often unsuccessful. DESIGN: Narrative review.